Ecophysiology of Chloromonas hindakii sp. nov. (Chlorophyceae), Causing Orange Snow Blooms at Different Light Conditions - Procházková, Lenka; Remias, Daniel; Řezanka, Tomáš; Nedbalová, Linda (Microorganisms, 2019)
Slowly melting snowfields in mountain and polar regions are habitats of snow algae. Orange blooms were sampled in three European mountain ranges. The cysts within the blooms morphologically resembled those of Chloromonas nivalis (Chlorophyceae). Molecular and morphological traits of field and cultured material showed that they represent a new species, Chloromonas hindakii sp. nov. The performance of photosystem II was evaluated by fluorometry. For the first time for a snow alga, cyst stages collected in a wide altitudinal gradient and the laboratory strain were compared. The results showed that cysts were well adapted to medium and high irradiance. Cysts from high light conditions became photoinhibited at three times higher irradiances (600 µmol photons m-2 s-1) than those from low light conditions, or likewise compared to cultured flagellates. Therefore, the physiologic light preferences reflected the conditions in the original habitat. A high content of polyunsaturated fatty acids (about 60% of total lipids) and the accumulation of the carotenoid astaxanthin was observed. They are regarded as adaptations to cope with extreme environmental conditions of snow that include low temperatures, freeze-thaw cycles, and variable light intensity. The intraspecific ability of adaptation of the photosynthetic apparatus to different irradiance regimes seems to be advantageous for thriving in different snow habitats.
Keywords: photosynthesis; fatty acids; environmental sample; cryoflora; cysts; astaxanthin